The Application of the Apostle Paul’s Teaching on Mutual Love Based on Romans 12:9–21 for the Congregation of the Bethel Church of Indonesia Sungai Yordan Telogah, Sanggau - Nomi Koseda; Paulus Sentot Purwoko; David Ming (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
Love is a fundamental principle in Christian life that should be expressed concretely within the church community. In practice, however, this teaching is not always fully internalized by believers. This study aims to examine the level of implementation of the Apostle Paul’s teaching on mutual love based on Romans 12:9–21 and to identify the most dominant contributing dimension among the congregation of Gereja Bethel Indonesia Sungai Yordan Telogah, Sanggau, West Kalimantan. Employing a quantitative survey method, data were collected from 26 respondents using a validated and reliable questionnaire and analyzed through descriptive statistics and simple linear regression. The results indicate that the implementation of mutual love is categorized as moderate. Regression analysis shows that the dimension of loving without demanding retaliation has the strongest influence, contributing 92.2% to the overall implementation, exceeding the dimension of brotherly love. This finding suggests that forgiveness-oriented love plays a central role in shaping congregational life. The study concludes that sustained pastoral teaching is necessary to deepen the internalization of Paul’s ethical teaching as a consistent spiritual character within the church.